Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Please help me solve this asap.... the correct answer is (x+y-5) Question is attatched

Please help me solve this asap.... the correct answer is (x+y-5)
 
 
Question is attatched

Question Image
Grade:12

1 Answers

Samyak Jain
333 Points
2 years ago
Given : a + xb + yc = 0   ...(1)  and  a x b + c + c x a = 6(c)         ...(2)
To solve this question, we’ll represent a in terms of b and c since RHS in second equation is in terms of (c).
We will use the facts that cross product of a vector with itself is a zero vector and negative of cross product
of a vector with another vector is same as cross product of second vector with the first i.e.
a x a = 0  and  – (a x b) = (b x a)
\because a + xb + yc = 0 ,  a = – (xb + yc)
Now, a x b = – (xb + yc) x b  =  – (x(b x b) + y(c x b))  =  – y(c x b)  =  y(b x c)  [\because b x b = 0]
&  c x a = x {– (xb + yc)} = – x (xb + yc)  =  – (x (c x b) + y(c x c)) = – x(c x b) = x(c x b)
[\because c x c = 0]
(2) becomes  y(b x c) + c + x(c x b)  =  6(c)  i.e.  
(x + y +1)(c)  =  6(c)
Comparing coefficients of c on both sides, we get
(x + y +1)  =  6  \Rightarrow  x + y – 5 = 0.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free